EFFECT OF GOOGLE CLASSROOM APPLICATION ON UNDERGRADUATE STUDENTS' SCORES IN EDUCATIONAL TECHNOLOGY IN UNIVERSITY OF CALABAR, NIGERIA - Ekpo-Eloma, Ekpo O.; Effiong, Abigail Aniefiok; Bisong , Anthony Etta; Udoh, Victoria Inebehe (Journal of Education and Practice, 2022)
Purpose: The study examined the effect of Google Classroom Application on undergraduate students' scores in Educational Technology in the University of Calabar, Nigeria. Methodology: Two null hypotheses were formulated to guide the study, Quasi-experimental research design using pre-test posttest non-randomized control group design was adopted for the study. The population is made up of al undergraduates offering Educational Technology as a course in the University of Calabar. A sample of 160 year two students of educational technology comprising of 85 female and 75 male were purposively sampled for the study. The Google Classroom Application and Educational Technology Performance Test (ETPT) were the instruments used for data collection. The results of the study were analyzed using Analysis of Covariance (ANCOVA). Findings: The results revealed that there is a significant difference in undergraduates students' scores in educational technology taught with the Google Classroom Application and those taught using expository method, there was also a significant difference in performance scores between male and female students taught using Google Classroom Application,. Unique contribution to theory, practice and policy: It was therefore recommended Google Classroom Application should be used always to promote students' academic performance in educational technology and that Lecturers should equally upgrade their skills on the utilization of Google classroom and other technological applications to stay afloat with 21st century skills online units best global practices.